Ways to increase the efficiency of agricultural clusters - Berdiyev Abdumalik Khakimovich (THE INNOVATION ECONOMY, 2026)
As a result of economic liberalization and the development of science and technology, fundamental changes are taking place in all sectors of our country, including the agricultural sector. The development of this sector is considered one of the most important priorities for both the state and society. The main reason for this is that the agricultural sector, in addition to addressing the country’s food security issues, serves as the primary source of raw materials for food industry enterprises. The clustering model in the agricultural sector is a mechanism that has repeatedly proven its effectiveness in global practice. Agro-clusters are associations of interrelated agricultural producers, processing enterprises, logistics services, educational and research institutions, as well as financial institutions, united within a single territorial system with the aim of creating high value-added products. In recent years, great attention has been paid in our Republic to the introduction of the cluster system, which has been tested by international practice and plays a significant role in the development and stability of the economy, as well as in the implementation of market relations and best practices. As a result, improving the efficiency of agro-clusters contributes to enhancing the overall competitiveness of agriculture, ensuring population employment, and strengthening the country’s export potential.